Relational contracting for construction excellence [ principles, practices and case studies - Chan, Albert P. C.; Chan, Daniel W. M.; Yeung, John F. Y. (Spon research, 2010)
Improved efficiency and effectiveness in the construction industry provide huge potential savings. Various forms of relational contracting such as partnering, alliancing, public private partnership